2017
DOI: 10.23876/j.krcp.2017.36.3.290
|View full text |Cite
|
Sign up to set email alerts
|

Numerical expression of volume status using the bioimpedance ratio in continuous ambulatory peritoneal dialysis patients: A pilot study

Abstract: BackgroundVolume overload results in higher mortality rates in patients on continuous ambulatory peritoneal dialysis (CAPD). The ratio of bioimpedance (RBI) might be a helpful parameter in adjusting dry body weight in CAPD patients. This study examined whether it is possible to distinguish between non-hypervolemic status and hypervolemic status in CAPD patients by using only RBI.MethodsRBI was calculated as follows: RBI = impedance at 50 kHz/impedance at 500 kHz. Based on the experts’ judgements, a total of 64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Nevertheless, these findings do not always provide an accurate assessment of volume status. [ 24 ] Accordingly a range of alternate methods are increasingly being adopted in an effort to provide more precise determinations of body fluid volume. Among these, bioimpedance techniques can estimate extracellular volume, intracellular volume, and total body water, whereas biochemical markers (such as atrial natriuretic and brain natriuretic peptides) can provide information concerning the intravascular filling state.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these findings do not always provide an accurate assessment of volume status. [ 24 ] Accordingly a range of alternate methods are increasingly being adopted in an effort to provide more precise determinations of body fluid volume. Among these, bioimpedance techniques can estimate extracellular volume, intracellular volume, and total body water, whereas biochemical markers (such as atrial natriuretic and brain natriuretic peptides) can provide information concerning the intravascular filling state.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that the ratio of bioimpedance (RBI) might be a helpful parameter to adjust dry weight in patients undergoing PD [ 56 ]. RBI was calculated as follows: RBI = impedance at 50 kHz / impedance at 500 kHz.…”
Section: Bia In Patients Undergoing Peritoneal Dialysismentioning
confidence: 99%
“…A multi-center study [ 7 ] evaluated the volume status of patients using a body composition monitor (BCM), and defined the ratio of excessive hydration (OH) to extracellular water (ECW) OH/ECW > 15% as volume overload based on BCM measurement results. The volume status of patients undergoing continuous ambulatory peritoneal dialysis (CAPD) can be simply represented by the ratio of bioimpedance (RBI), which is the impedance at 50 kHz/the impedance at 500 kHz [ 8 ]. When BCM analysis cannot be used, RBI can be used as an alternative.…”
Section: Discussionmentioning
confidence: 99%